Efforts to Improve Obligatory Prayer Skills Through Practice and Contextual Learning in Class 7 of MTs Jam'iyyah Muhammadiyah Tanjung Pura - Rafif Taufiqurrahman; Irawati Rahma; Usmaidar; Enni Suhenni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to identify efforts to improve fardhu prayer skills through contextual learning among seventh-grade students at MTs Jam'iyyah Muhammadiyah. The research employs a classroom action research method, with data collection techniques including observation, interviews, field notes, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that fardhu prayer skills among students improved through contextual learning, which connects the material to students' real- life experiences, enabling them to understand, apply, and correctly perform the movements and recitations of the fardhu prayer. The teacher's efforts to enhance students' prayer skills involved using contextual learning, which effectively increased students' proficiency in performing fardhu prayers in the fiqh subject. In the first cycle, students' abilities were categorized as